2022
DOI: 10.1111/pbr.13053
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating genetic variability and genotype × environment interactions for grain iron and zinc content among diverse genotypes of lentils (Lens culinaris)

Abstract: Micronutrient malnutrition is a great burden towards attaining nutritional security for the vulnerable section of society, especially pregnant and lactating women, as well as preschool children in developing countries. Biofortification of lentil with iron (Fe) and zinc (Zn) may have a great impact on health and nutritional security as this food legume is the chief source of dietary energy and easily digestible protein for the vegetarian population. Assessment of genetic variability followed by ciphering genoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Several factors are at play during nutrient homeostasis and this complex network involves multiple genes and transcription factors that vary from genotype to genotype leading to genotypic variation. Moreover, further research suggested the existence of quantitative traits modulating the pathway revealing the importance of understanding the GE interaction, which impacted the results of genetic analysis for these complex traits (Bhattacharya et al, 2022b).…”
Section: Appraisal Of Stable Lentil Genotypesmentioning
confidence: 99%
See 2 more Smart Citations
“…Several factors are at play during nutrient homeostasis and this complex network involves multiple genes and transcription factors that vary from genotype to genotype leading to genotypic variation. Moreover, further research suggested the existence of quantitative traits modulating the pathway revealing the importance of understanding the GE interaction, which impacted the results of genetic analysis for these complex traits (Bhattacharya et al, 2022b).…”
Section: Appraisal Of Stable Lentil Genotypesmentioning
confidence: 99%
“…L1 (6.06) and L2 (5.92) were identified as 'ideal' or type-I locations for appraisal of precious genotypes in case of grain Fe and Zn content, respectively considering the highest "desirability index" (Table 3). Over the years, Bhattacharya et al (2022b) have utilised the HA-GGE biplot for appraisal of genotypes and environment. In addition to this, the adequacy and accountability of the methodology combined with the overall environmental influence, which is portrayed by the vector projection on the "AEC abscissa" is an indirect selection criterion for self-pollinated crops like lentil as the additive component of variation is predominant (Yan and Holland, 2010).…”
Section: Delimitation Of Ideal Test Locationmentioning
confidence: 99%
See 1 more Smart Citation
“…To further restrict our analysis to research prominently conducted in Africa, only 48 publications were retained for further analysis, i.e., those with first and/or corresponding authors affiliated with an African country ( Table 1 , plant species and references in bold). Hence, 22 papers were excluded, as they either did not report an African affiliation as a prominent authorship [ 15 , 19 , 20 , 27 , 28 , 35 , 36 , 41 , 42 , 53 , 56 , 59 , 70 , 71 , 73 , 78 , 81 , 82 , 85 ], or the first author did not have an African affiliation, and there was no clear African research leadership due to the presence of at least three corresponding authors [ 43 , 60 , 69 ].…”
Section: Plant Fe Research Prominently Conducted In Africa From 2018 ...mentioning
confidence: 99%
“…Thus, these areas all together accounted for 80%-90% of the total area under lentil production in India (FAOSTAT, 2021). This food legume is a crucial component of cereal-based cropping system of IGP (Bhattacharya et al, 2022a, Bhattacharya et al, 2022b. However, the average productivity of lentil in IGP is low due to several biotic constraints and farmers being sceptical of converting the traditional rice-based monocropping system to a more productive rice-lentil cropping system.…”
Section: Introductionmentioning
confidence: 99%